8(3x-1)=2(2x+6)

Simple and best practice solution for 8(3x-1)=2(2x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(3x-1)=2(2x+6) equation:



8(3x-1)=2(2x+6)
We move all terms to the left:
8(3x-1)-(2(2x+6))=0
We multiply parentheses
24x-(2(2x+6))-8=0
We calculate terms in parentheses: -(2(2x+6)), so:
2(2x+6)
We multiply parentheses
4x+12
Back to the equation:
-(4x+12)
We get rid of parentheses
24x-4x-12-8=0
We add all the numbers together, and all the variables
20x-20=0
We move all terms containing x to the left, all other terms to the right
20x=20
x=20/20
x=1

See similar equations:

| 7c-9=-1+9c | | −4x+6=−26 | | f-6=-43 | | 2^(x)(7)=28 | | 3m+8=4+4m | | (3x+1)=12x | | 1.9-9.98-2.5k=4.88-0.5k | | 9x+7=-7-2(4x+2) | | 7n+-1÷2=140 | | 10+3n=6n-n | | -7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x-22=4x-7x | | -3y+7=4y-7 | | b-7/7=7 | | 210+t=9 | | ½(6+x)=x+4 | | -5(n+6)=6(2-2n) | | 7-4z=-6z-9 | | -16+j=32 | | 8f–12=5f+12 | | n/3+45=52 | | 13-3p=-(-4+6p) | | x+(-4)=(-18) | | -5w-5+6w=2+2w | | 6x-4+2(5x-2)=16x | | 35√y+2=9 | | 470÷x= | | 6m+5=4m-2 | | 2h+10=-9-h+7 | | -8(8+5m)=8(7-8m) | | 3n+10=3(12) | | 1-3m=-14-6m | | 8+9t=-8+3t+8t |

Equations solver categories